Penerapan Model Picture And Picture Untuk Meningkatkan Kemampuan Menulis Gambar Bercerita Peserta Didik Kelas V SDN 1 Srirande - Mayske Rinny Liando; Grace Engelin Kuron; Putri Yeni Lestari (JUPE : Jurnal Pendidikan Mandala, 2022)
One type of writing skill is writing pictures telling stories. This skill is a skill that can hone or train to convey ideas or ideas in his mind through pictures. The pictures that have been written form a sequential story. The results of an interview with one of the educators at SDN 1 Srirande found that in learning to write storytelling pictures there were still many students who scored below the minimum completeness criteria (KKM) with the minimum completeness criteria value for writing stories was 70. The type of research used in this study is classroom action research (CAR). The purpose of classroom action research is to improve the implementation of the learning process in education, especially in classroom learning and student learning outcomes. Based on the results of the research and discussion that has been presented, it can be concluded that there has been an increase in storytelling picture writing skills using the picture and picture learning model where in the first cycle the percentage value of the students' storytelling picture writing skills was 50% in the less category, while there was an increase in the first cycle. II where the results of students' storytelling picture writing skills with a percentage value of 100% with a very good category.